Genetic Characterization, Antibiotic Resistance, and Virulence Genes Profiling of Bacillus cereus Strains from Various Foods in Japan - Marwa Nabil Sayed Abdelaziz; Mahmoud Gamaleldin Zayda; Aye Thida Maung; Mohamed El-Telbany; Tahir Noor Mohammadi; Su Zar Chi Lwin; Khin Zar Linn; Chen Wang; Lu Yuan; Yoshimitsu Masuda; Ken-ichi Honjoh; Takahisa Miyamoto (MDPI AG, 2024)
Bacillus cereus sensu stricto is a foodborne pathogen that causes food poisoning. Their spore and biofilm-forming abilities persist in various environments and foods. This study investigated the prevalence, virulence, antibiotic resistance, and genetic diversity of B. cereus s. s. strains isolated from various food samples. Of 179 samples, 22.34% were positive for B. cereus s. s., with significantly high detection rates in milk products and raw chicken meat. Forty strains were isolated from positive samples. Matrix-assisted laser desorption ionization/time of flight mass spectrometry analysis revealed nine distinct clusters and multi-locus sequence typing revealed 34 sequence types including 23 novel sequences, demonstrating high genetic diversity among the isolates. PCR analysis revealed that all the strains contained at least one toxin gene, but none contained the cytK gene. Antibiotic resistance tests revealed that all isolates were classified as multidrug-resistant, with high resistance levels, particularly to β-lactam antibiotics and vancomycin, but were susceptible to gentamicin. All isolates showed variations in biofilm formation. This study highlights the significant public health risk due to B. cereus s. s. and underscores the need for stringent monitoring and control measures in food production to manage antimicrobial resistance and ensure food safety.